Karakteristik demografi penderita kandidiasis vulvovaginalis pada wanita hamil - Riska Afrianty; Irwan Fahri Rangkuti; Yostoto B Kaban (Fakultas Kedokteran USU, 2013)
Introduction : Candidiasis vulvovaginalis (KVV) in pregnancy is a vaginal infection in pregnant women caused by candida albicans or other candida species that infect the vagina and or vulva, giving rise to the complaints of vaginal discharge in the body. Several studies in Indonesia shows the demographic characteristics of patients with vaginal candidiasis were varied.However KVV demographic characteristics in pregnant women have not been done the research.Purpose : To determine the demographic characteristics of patients with candidiasis picture vulvovaginalis in pregnant women Methods: The study was descriptive cross sectional study that was conducted in November 2012 - February 2013, involving 54 pregnant women with KVV.Results: The number of patients KVV in pregnant women aged from 26-30 years as many as 16 people (29.6%), high school education were 20 people (37%), housewives work totaling 33 people (61.1%), 46 people (85.2%) were married status, ethnic Batak and Javanese are the largest tribe (respectively 33% and 27.8%). Gestational age is the most visits in the third trimester as many as 26 people (48.1%), vaginal pH levels participate bertururt 4.5, 5, and 5.5 amounts to the same, namely 18 persons (33.3%).Conclusion : Distribution KVV on pregnant women aged from 26-30 years old, high school education, work-home mom, married status, tribe Batak and Javanese are the largest tribe. Gestational age most visits are in the third trimester, vaginal pH levels participate bertururt 4.5, 5, and 5.5 amounts to the same.Keywords : characteristics; candidiasis vulvovaginalis; pregnant